Peripheral Antihypertensive Mechanisms Of Zing/Ber Officinale Var. Rubrumin Spontaneously Hypertensive Rats - Razali, Nadiah (2022)
Hypertension has been associated with end-organ damage that may eventually lead to stroke, heart, and renal failure. Blood pressure variability is possibly the most important determining factor for the end-organ damage. Zingiber officinale var. rubrum (ZOVR) (Halia bara) is a Malay traditional medicine claimed to have antihypertensive effects. This study investigated the effects of ZOVR (250 mg/kg b.w) on vascular responsiveness and reactivity in spontaneously hypertensive rats (SHRs) and the mechanisms involved. SHRs were orally fed daily for 28 days with ZOVR extracts and non-invasive systolic blood pressure, mean arterial pressure, heart rate and body weight were measured. Vascular reactivity and responsiveness were assessed using isolated aortic rings, anaesthetised non- and pithed rats, respectively. Appropriate agonists and antagonists (L-NAME, indomethacin, methylene blue, atropine, glibenclamide, hexamethonium, prazosin and propranolol) for the mechanism study were employed. All three crude extracts of ZOVR significantly reduced the mean arterial pressure (MAP) of SHRs in comparison or comparable with verapamil during the 28-day daily oral feeding of ZOVR extracts, with petroleum ether extract (ZOP) produced the most antihypertensive effect and selected for fractionation.